Voice into acting integrating voice and the Stanislavski approach - Gutekunst, Christina; Gillett, John (Methuen Drama, 2021)
"How can actors bridge the gap between themselves and the text and action of a script, integrating fully their learned vocal skills? How do we make an imaginary world real, create the life of a role, and fully embody it vocally and physically so that voice and acting become one? Christina Gutekunst and John Gillett unite their depth of experience in voice training and acting to create an integrated and comprehensive approach informed by Stanislavski and his successors - the acting approach widely taught to actors in drama schools throughout the world. This updated edition contains: a new section on vocal embodiment of actions, new findings from neuroscience as evidence of the science behind the approach, more exercises and warm-up routines for training, pre-rehearsal and pre-performance. The authors create a step-by-step guide to explore how voice can: - Respond to our thoughts, senses, feelings, imagination and will - Fully express language in content and form - Communicate imaginary circumstances and human experience - Transform to adapt to different roles - Connect to a variety of audiences and spaces Featuring 55 illustrations by German artist, Dany Heck, Voice into Acting is an essential manual for the actor seeking full vocal identity in characterization, and for the voice teacher open to new techniques or an alternative approach to harmonize with the actor's process"-- Provided by publisher.